Jet production in ep collisions at high Q2 and determination of αs - Aaron, Francisc Dionisie; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2010)
The production of jets is studied in deep-inelastic e ± p scattering at large negative four momentum transfer squared 150<Q 2<15000 GeV2 using HERA data taken in 1999–2007, corresponding to an integrated luminosity of 395 pb−1. Inclusive jet, 2-jet and 3-jet cross sections, normalised to the neutral current deep-inelastic scattering cross sections, are measured as functions of Q 2, jet transverse momentum and proton momentum fraction. The measurements are well described by perturbative QCD calculations at next-to-leading order corrected for hadronisation effects. The strong coupling as determined from these measurements is αs(MZ)=0.1168±0.0007(exp.)+0.0046−0.0030(th.)±0.0016 (PDF).
Online publiziert: 24 November 2009
*The H1 Collaboration: F.D. Aaron, A. Schöning, H.-C. Schultz-Coulon [und 250 weitere Personen]
Im Titel ist die Zahl 2 hochgestellt
Im Titel ist der Buchstabe s tiefgestellt
Gesehen am 15.11.2022